Needs Assessment for a Provincial Literacy Hotline Service - Bell, Jim. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
A study was conducted to determine the need for a provincewide literacy hotline in Alberta, Canada, and if needed, the configuration of services for establishing the hotline. Data were gathered through two surveys. In order to find out what an Alberta literacy hotline service might look like, a cross-Canada telephone and mail survey was conducted. Different questionnaires were designed and distributed to 217 administrators, instructors, and students in literacy and English as a Second Language courses in Alberta; 156 questionnaires were returned (72 percent). The cross-Canada telephone survey of approximately 10 persons who had been involved with literacy hotlines confirmed 7 functions such hotline services might perform: refer interested adults to literacy programs; refer interested adults to programs in English as a Second Language; refer potential volunteers to programs; provide general literacy information to the interested public; distribute literacy information to the literacy community; provide advice to literacy workers; and raise public awareness and understanding of adult literacy issues. It also revealed that literacy hotlines are a relatively new phenomenon, vary widely in form and function, can certainly fail, and generally thrive on advertising. The survey of Alberta gathered information on the present state of affairs related to each of the services a hotline could provide. From the findings of this survey, it was concluded that there does seem to be a need for a provincial hotline service in Alberta, but only if it takes a certain shape, making its first priority public awareness and understanding, and its secondary concern referring students and volunteers to programs. After establishing and defining the need, the next step is to determine whether there is enough funding for enough years to warrant starting the service. (The survey instruments and 11 references are included in this report.) (KC)
Sponsoring Agency: Alberta Association for Adult Literacy, Calgary.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Adult Programs; English (Second Language); Foreign Countries; Hotlines (Public); Information Needs; Information Sources; Literacy Education; Needs Assessment; Outreach Programs; Publicity; Second Language Instruction; Alberta; Reports, Research; Tests/Questionnaires.